Analysis of Human Resource Management in the Polbeng Business Expo Through Traditional and Contemporary Costume Fashion Show - Anita Rinanda; Wan Junita Raflah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Human Resource Management (HRM) plays a crucial role in ensuring the successful implementation of project-based events, particularly those involving student organizations. This study aims to analyze the implementation of the Human Resource Planning System Model in organizing the Traditional and Contemporary Costume Fashion Show at the Polbeng Business Expo. The research employed a descriptive qualitative method with a project-based approach to obtain an in-depth understanding of human resource planning, implementation, and evaluation throughout the event. Data were collected through direct observation, semi-structured interviews, and documentation involving key informants, namely the Human Resource Committee Coordinator and the Project Manager. The collected data were analyzed using the qualitative data analysis model proposed by Miles, Huberman, and Saldaña (2014), while the analytical framework was based on Sikula's (1981) Human Resource Planning System Model, consisting of Human Resource Objectives, Human Resource Planning, Human Resource Budget, Human Resource Estimate, Human Resource Activity Programs, and Evaluation and Feedback. The findings reveal that systematic implementation of these six components significantly contributed to effective task allocation, improved communication, stronger coordination among committee members, efficient budget utilization, and better operational readiness during the event. Furthermore, continuous evaluation and feedback enabled the organizing committee to identify strengths, address operational challenges, and improve future event planning. The study concludes that the Human Resource Planning System Model is applicable and effective in managing student-led educational events. The findings provide both theoretical contributions to the field of human resource management in project-based event organizations and practical recommendations for enhancing future Polbeng Business Expo activities through more structured, coordinated, and sustainable human resource management practices.